2016
DOI: 10.1038/srep26155
|View full text |Cite
|
Sign up to set email alerts
|

Memristive Sisyphus circuit for clock signal generation

Abstract: Frequency generators are widely used in electronics. Here, we report the design and experimental realization of a memristive frequency generator employing a unique combination of only digital logic gates, a single-supply voltage and a realistic thresholdtype memristive device. In our circuit, the oscillator frequency and duty cycle are defined by the switching characteristics of the memristive device and external resistors. We demonstrate the circuit operation both experimentally, using a memristor emulator, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The introduction of resistive switching (RS) devices (also called memristors) to the set of standard electronic components is expected to enrich significantly the landscape of modern circuit design and development [1][2][3][4][5]. The memristor has been known as the fourth fundamental circuit element ever since Leon Chua postulated its existence in 1971 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of resistive switching (RS) devices (also called memristors) to the set of standard electronic components is expected to enrich significantly the landscape of modern circuit design and development [1][2][3][4][5]. The memristor has been known as the fourth fundamental circuit element ever since Leon Chua postulated its existence in 1971 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The paper differs from existing papers in the literature where the memristor oscillators use ideal, abstract, or artificial memristor models, that cannot accurately describe the behavior of real memristor devices implemented in nanotechnology [24]. The approach in the manuscript to implement an oscillator is also basically different from the quoted papers in the literature [7], [37], [39] where the oscillations are built upon the hysteresis loops displayed by the memristor in the v − i plane. In that case, the memristor is not a programmable nonlinear resistor, rather the state variable undergoes wide variations during the transient oscillations.…”
Section: Introductionmentioning
confidence: 84%
“…Similarly, [38] investigated the nonlinear dynamics and bifurcations in a modified Shinriki oscillatory circuit also using a Knowm memristor. We also mention the article [39] that reports on the design and experimental realization of a memristive frequency generator with digital logic gates, a single-supply voltage and a threshold-type non-volatile memristive device.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, some reported memristor-based artificial neural networks have shown that these developments may become feasible in the near future, at least in relatively small scale (Alibart and Zamanidoost, 2013; Garbin et al, 2014; Prezioso et al, 2015). With the development of integration techniques for large scale memristor crossbar or even 3D networks (Yu et al, 2013; Li et al, 2016), as well as memristor for logical or arithmetical computations (Borghetti et al, 2010; Gale, 2015) to reduce complex peripheral circuits by replacing the digital neurons, we envisage a real chip able to perform interesting memory tasks.…”
Section: Discussionmentioning
confidence: 99%